Justice Is Always a Relational Matter. On Forst’s Normativity and Power - Oana Crusmac (University of Groningen Press, 2020)
Review of Rainer Forst (2017) Normativity and Power. Analyzing Social Orders of Justification. Oxford: Oxford University Press.